Implementasi Strategi Dakwah Dalam Program Pemulihan Mental Korban Judi Online Pada Lembaga Rehabilitas Khalid Bin Walid Medan - Haliza Nur Sa’diah; Soiman (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the implementation of da'wah strategies in the mental recovery of online gambling victims at the Khalid bin Walid Islamic Rehabilitation Institute in Medan, focusing on the application of strategies, rehabilitation programs, and their impact on participants' mental and behavioral changes. Unlike previous studies that largely discussed drug rehabilitation, this research offers a da'wah-based rehabilitation model that integrates spiritual guidance, psychological counseling, and character building as a holistic approach to recovering online gambling victims. The method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, participant observation, and documentation involving ustadz, coaches, and rehabilitation participants. The results show that da'wah strategies are implemented through daily worship habituation, Islamic studies, personal mentoring, and continuous supervision. The mental recovery program is carried out in stages through adaptation, worship guidance, addiction counseling, group therapy, and family relationship development. The implementation of this strategy has proven to increase spiritual awareness, self-control, discipline, and encourage positive behavioral changes among participants. Thus, da'wah-based rehabilitation with an integrative approach is effective in supporting the mental recovery of online gambling victims and can serve as an alternative model in addressing behavioral addiction in the digital era